The Use of Bamboo Biochar as a Soil Improver on the Growth and Yield of Mustard Plants - Yohanes Parlindungan Situmeang (Agriwar Journal, 2022)
This study aims to obtain the right dose of biochar in mustard plants. The design used was a completely randomized design with a one-factor pattern. The biochar treatment was studied at four dose levels and one control. The application of biochar significantly affected plant height, total fresh weight, and total dry weight, except for the number of leaves which was not significant. The highest total dry weight yield was achieved at 9 t ha-1 biochar with a weight of 10.80 g or an increase of 60% compared to 6.75 g without biochar. From the regression analysis, the effect of biochar on total dry weight was found on the quadratic regression line with the equation: Å¶ = 6.717 + 0.8217 X - 0.04381 X2 (R2 = 91.80%), biochar with an optimal dose of 9.38 t ha -1 and a maximum total dry weight of 10.70 g.